Long-read sequencing and genome assembly of natural history collection samples and challenging specimens - Bernhard Bein; Ioannis Chrysostomakis; Larissa S. Arantes; Tom Brown; Charlotte Gerheim; Tilman Schell; Clément Schneider; Evgeny Leushkin; Zeyuan Chen; Julia Sigwart; Vanessa Gonzalez; Nur Leena W. S. Wong; et al. (Genome Biology)
Abstract Museum collections harbor millions of samples, largely unutilized for long-read sequencing. Here, we use ethanol-preserved samples containing kilobase-sized DNA to show that amplification-free protocols can yield contiguous genome assemblies. Additionally, using a modified amplification-based protocol, employing an alternative polymerase to overcome PCR bias, we assemble the 3.1 Gb maned sloth genome, surpassing the previous 500 Mb protocol size limit. Our protocol also improves assemblies of other difficult-to-sequence molluscs and arthropods, including millimeter-sized organisms. By highlighting collections as valuable sample resources and facilitating genome assembly of tiny and challenging organisms, our study advances efforts to obtain reference genomes of all eukaryotes.